Identification of phenolic secondary metabolites from Schotia brachypetala Sond. (Fabaceae) and demonstration of their antioxidant activities in Caenorhabditis elegans - Sobeh, Mansour; Peixoto, Herbenya; Sharopov, Farukh; Mohamed, Tamer; Krstin, Sonja; Wink, Michael (PeerJ, 2016)
Background Schotia brachypetala Sond. (Fabaceae) is an endemic tree of Southern Africa whose phytochemistry and pharmacology were slightly studied. The present work aimed at profiling the major phenolics compounds present in the hydro-alcohol extract from S. brachypetala leaves (SBE) using LC/HRESI/MS/MS and NMR and prove their antioxidant capabilities using novel methods. Methods In vitro assays; DPPH, TEAC persulfate decolorizing kinetic and FRAP assays, and in vivo assays: Caenorhabditis elegans strains maintenance, Intracellular ROS in C. elegans, Survival assay, GFP expression and Subcellular DAF-16 localization were employed to evaluate the antioxidant activity. Results More than forty polyphenols, including flavonoid glycosides, galloylated flavonoid glycosides, isoflavones, dihydrochalcones, procyanidins, anthocyanins, hydroxy benzoic acid derivatives, hydrolysable tannins, and traces of methylated and acetylated flavonoid derivatives were identified. Three compounds were isolated and identified from the genus Schotia for the first time, namely gallic acid, myricetin-3-O-α-L-1C4-rhamnoside and quercetin-3-O-L-1C4-rhamnoside. The total phenolics content of SBE was (376 mg CAE/g), followed by flavonoids (67.87 QE/g). In vitro antioxidant activity of SBE was evidenced by DPPH radical scavenging activity (IC50 of 9 µg/mL), FRAP ferric reducing activity (5,000 mol Fe2+ E/mg) and ABTS peroxide inhibiting activity (1,054 mM Trolox E/mg). The tested extract was able to protect the worms against juglone induced oxidative stress, an increased survival rate (up to 41%) was recorded, when compared with the control group (11%) and attenuate the reactive oxygen species (ROS) accumulation in dose-dependent and reached up to 72% for the highest tested concentration. SBE was also able to attenuate the levels of heat shock protein (HSP) expression in dose-dependent up to 60% in the 150 µg SBE/mL group. In DAF-16 Subcellular localization SBE treated worms showed nuclear localization pattern up to 78%, while it was only 5% in the untreated control group. Discussion A pronounced antioxidant activity in vivo, which can be attributed to its ability to promote the nuclear translocation of DAF-16/FOXO, the main transcription factor regulating the expression of stress response genes. The remarkable antioxidant activity in vitro and in vivo correlates to SBE rich phenolic profile.
Gesehen am 08.05.2020